Advanced materials and technologies for oral diseases - Hao Cui; Yan You; Guo-Wang Cheng; Zhou Lan; Ke-Long Zou; Qiu-Ying Mai; Yan-Hua Han; Hao Chen; Yu-Yue Zhao; Guang-Tao Yu (Science and Technology of Advanced Materials, 2023)
ABSTRACT Oral disease, as a class of diseases with very high morbidity, brings great physical and mental damage to people worldwide. The increasing burden and strain on individuals and society make oral diseases an urgent global health problem. Since the treatment of almost all oral diseases relies on materials, the rapid development of advanced materials and technologies has also promoted innovations in the treatment methods and strategies of oral diseases. In this review, we systematically summarized the application strategies in advanced materials and technologies for oral diseases according to the etiology of the diseases and the comparison of new and old materials. Finally, the challenges and directions of future development for advanced materials and technologies in the treatment of oral diseases were refined. This review will guide the fundamental research and clinical translation of oral diseases for practitioners of oral medicine.